In vivo mucosal delivery of bioactive human interleukin 1 receptor antagonist produced by Streptococcus gordonii - Ricci, Susanna (BioMed Central, 2003)
BACKGROUND: Interleukin-1 (IL-1) is a cytokine involved in the initiation and amplification of the defence response in infectious and inflammatory diseases. IL-1 receptor antagonist (IL-1ra) is an inactive member of the IL-1 family and represents one of the most potent mechanisms for controlling IL-1-dependent inflammation. IL-1ra has proven effective in the therapy of acute and chronic inflammatory diseases in experimental animal models and also in preliminary clinical trials. However, optimisation of therapeutic schedules is still needed. For instance, the use of drug delivery systems targeting specific mucosal sites may be useful to improve topical bioavailability and avoid side effects associated with systemic administration. RESULTS: In order to develop systems for the delivery of IL-1ra to mucosal target sites, a Streptococcus gordonii strain secreting human IL-1ra was constructed. The recombinant IL-1ra produced by S. gordonii was composed of the four amino acid residues RVFP of the fusion partner at the N-terminus, followed by the mature human IL-1ra protein. RFVP/IL-1ra displayed full biological activity in vitro in assays of inhibition of IL-1β-induced lymphocyte proliferation and was released by recombinant S. gordonii in vivo both at the vaginal and the gastrointestinal mucosa of mice. RFVP/IL-1ra appeared beneficial in the model of ulcerative colitis represented by IL-2(-/- )mice (knock-out for the interleukin-2 gene), as shown by the body weight increase of IL-2(-/- )mice locally treated with S. gordonii producing RFVP/IL-1ra. CONCLUSIONS: These results indicate that recombinant S. gordonii can be successfully used as a delivery system for the selective targeting of mucosal surfaces with therapeutic proteins.